Smart-Specialization of Hotel Services - Сидорук, Світлана Володимирівна; Поліщук, Лариса Миколаївна; Тищук, Інна Володимирівна (Київський національний університет імені Тараса Шевченка, 2019)
Goal. The main goal is the process of forming the smart specialization of hotel services as one of the elements of the concept of intelligent integration for the management of hotel infrastructure. Method. In researching the smart specialization of hotel services, quantitative and qualitative methods of evaluation were used. One of them is a naïve-forecast assumption that the future value of the indicator will correspond to last year's same period of time with an adjustment of ± 5%. Na'ive-forecast was adjusted by distinguishing the factor of seasonality, which is typical for hotel business in the modern economic environment. Results. The study of the availability of hotel establishments for tourists, transitists, businessmen of the region in the system of smart specialization of hotel services, which can become the basis for creating a special image of the region and provide him with certain competitive advantages. Scientific novelty. The foreign experience in using Smart City has been analyzed. Based on elements of Smart City, the priority directions of development of smart specialization of hotel services have been formed. The analysis of the stakeholders in the region (local state administrations, travel agencies, sports organizations, regional development agencies, politicians, residents of the region, consulting companies, representatives of creative professions of the region, chambers of commerce and industry, trade and economic missions in the diplomatic missions of Ukraine abroad) ) from the effect of introducing the smart specialization of hotel services. The forecast for the development of smart specialization of hotel services on the basis of naïve approach is carried out. For the first time, smart specialization was adapted to the sphere of hotel services in view of future achievements. The offered approaches will promote increase of efficiency of introduction of smart specialization of hotel services by increase of profit of hotel establishments, index of satisfaction of clients from use of hotel services. Practical significance. The offered approaches will promote increase of efficiency of introduction of smart specialization of hotel services by increase of profit of hotel establishments, index of satisfaction of clients from use of hotel services. The use of advanced automated systems will increase the number of hotel guests, and will encourage initiative groups and organizations that act as developers of innovative models of functioning of the modern hotel space and the creation of a comprehensive strategy and data platforms for the implementation of deve.

Мета. Процес формування смарт-спеціалізації готельних послуг в наш час розглядається як сукупність елементів концепції розумної інтеграції для управління готельною інфраструктурою. Методика. При дослідженні смарт-спеціалізації готельних послуг використовувалися кількісні та якісні методи оцінки. Одним із них є naїve-прогноз припущення про те, що майбутнє значення показника буде відповідати минулорічному за цей самий період часу з коригуванням на ±5 %. Naїve-прогноз коригувався шляхом виокремлення чинника сезонності, що є характерним для ведення готельного бізнесу в сучасному економічному середовищі. Результати. Вивчено доступність готельних закладів для туристів, транзитників, бізнесменів регіону в системі смарт-спеціалізації готельних послуг, що може стати основою для створення особливого іміджу регіону і забезпечити йому певні конкурентні переваги. Проаналізовано зарубіжний досвід щодо використання Smart City. На основі елементів Smart City, сформовано пріоритетні напрями розвитку смартспеціалізації готельних послуг. Науково новизна. Проаналізовано зацікавлені сторони у регіоні (місцеві державні адміністрації, туристичні агентства, спортивні організації, агенції регіонального розвитку, політичні діячі, жителі регіону, консалтингові компанії, представники креативних професій регіону, торгово-промислові палати, торгівельно-економічні місії у складі дипломатичних представництв України за кордоном ) від ефекту впровадження смартспеціалізації готельних послуг. Проведено прогноз щодо розвитку смартспеціалізаціїї готельних послуг на основі naїve-підходу. Наукова новизна. Вперше адаптовано смарт-спеціалізацію до сфери готельних послуг на баченні майбутніх досягнень. Практична значимість. Запропоновані підходи сприятимуть підвищенню ефективності впровадження смарт-спеціалізації готельних послуг шляхом збільшення прибутку готельних закладів, індексу задоволення клієнтів від використання готельних послуг. Застосування передових автоматизованих систем збільшить кількість гостей готельних закладів, а також заохотить ініціативні групи і організації, які виступають в ролі розробників інноваційних моделей функціонування сучасного готельного простору та створення всеосяжної стратегії і платформ даних для реалізації проектів розвитку смарт-спеціалізації регіону.

Цель. Главной целью является процесс формирования смарт-специализации гостиничных услуг как одного из элементов концепции разумной интеграции для управления гостиничной инфраструктурой. Методика. При исследовании смарт-специализации гостиничных услуг использовались количественные и качественные методы оценки. Одним из них является naиve-прогноз предположение о том, что будущее значение показателя будет соответствовать прошлогоднему за этот же период времени с корректировкой на ± 5%. Naиve-прогноз корректировался путем выделения фактора сезонности, что характерно для ведения гостиничного бизнеса в современной экономической среде. Результаты. Изучено доступность гостиничных заведений для туристов, транзитников, бизнесменов региона в системе смарт-специализации гостиничных услуг, может стать основой для создания особого имиджа региона и обеспечить ему определенные конкурентные преимущества. Проанализирован зарубежный опыт по использованию Smart City. На основе элементов Smart City, сформирован приоритетные направления развития смарт-специализации гостиничных услуг. Научная новизна. Проанализированы заинтересованные стороны в регионе (местные государственные администрации, туристические агентства, спортивные организации, агентства регионального развития, политические деятели, жители региона, консалтинговые компании, представители креативных профессий региона, торгово-промышленные палаты, торгово-экономические миссии в составе дипломатических представительств Украины за рубежом) от эффекта внедрения смартспециализации гостиничных услуг. Проведен прогноз по развитию смартспециализации и гостиничных услуг на основе naиve-подхода. Впервые адаптировано смарт-специализацию в сферу гостиничных услуг на видении будущих достижений. Практическая значимость. Предложенные подходы будут способствовать повышению эффективности внедрения смарт-специализации гостиничных услуг путем увеличения прибыли гостиничных заведений, индекса удовлетворенности клиентов от использования гостиничных услуг. Применение передовых автоматизированных систем увеличит количество гостей гостиничных заведений, а также поощрит инициативные группы и организации, которые выступают в роли разработчиков инновационных моделей функционирования современного гостиничного пространства и создания всеобъемлющей стратегии и платформ данных для реализации проектов развития смарт-специализации региона.
Смарт-спеціалізація готельних послуг
Смарт-специализация гостиничные услуги
Keywords: готельний заклад; смарт-спеціалізація; клієнт; досвід; турист; транзитник; бізнесмен; гостиничный заведение; смарт-специализация; клиент; опыт; бизнесмен; hotel institution; smart specialization; client; experience; tourist; transit; businessman